Efektivitas dan Kontribusi Pajak Daerah Dalam Upaya Peningkatan Pendapatan Asli Daerah Kota Padang Tahun Anggaran 2020-2024 - Mulyani, Fitrah; Fatdilah, Sari (Universitas Dharma Andalas, 2025)
This study discusses the effectiveness and contribution of regional taxes in efforts to increase the original regional income of Padang City for in the 2020-2024 budget year. This study aims to determine the effectiveness and contribution of regional taxes in efforts to increase the original regional income of Padang City in 2020-2024. This study uses the effectiveness ratio of Padang City regional taxes in 2020- 2024 and the ratio of regional tax contributions in efforts to increase the original regional income of Padang City in 2020-2024. The effectiveness ratio is seen by comparing the realization of regional taxes with the target of regional taxes multiplied by 100%, while the ratio of regional tax contributions is done by dividing the realization of regional taxes by the realization of original regional income multiplied by 100%. Based on the effectiveness ratio of Padang City regional taxes in 2020-2024 as a whole, it is in the less effective category because Covid-19 still has a significant impact on the original regional income of Padang City in 2020-2024. The ratio of regional tax contributions in efforts to increase the original regional income of Padang City in 2020-2024 is in the very good category. It can be concluded that the development of the effectiveness and contribution of regional taxes in efforts to increase the original regional income of Padang City is improving from year to year. The Padang City Government is expected to further explore regional potential in efforts to increase regional tax collection to be more effective from year to year, so that regional taxes make a large contribution to the Original Regional Income of Padang City. Abstrak Penelitian ini membahas mengenai efektivitas dan kontribusi pajak daerah terhadap pendapatan asli daerah Kota Padang Tahun Anggaran 2020-2024. Penelitian ini bertujuan untuk mengetahui efektivitas dan kontribusi pajak daerah dalam upaya peningkatan pendapatan asli daerah Kota Padang tahun 2020-2024. Penelitian ini menggunakan rasio efektivitas pajak daerah Kota Padang tahun 2020-2024 dan rasio kontribusi pajak daerah dalam upaya peningkatan pendapatan asli daerah Kota Padang tahun 2020-2024. Rasio efektivitas dilihat dengan cara melakukan perbandingan realisasi pajak daerah dengan target pajak daerah di kali 100%, sedangkan rasio kontribusi pajak daerah dilakukan dengan cara realisasi pajak daerah dibagi dengan realisasi pendapatan asli daerah dikali 100%. Berdasarkan rasio efektivitas pajak daerah Kota Padang tahun 2020-2024 secara keseluruhan berada dalam kategori kurang efektif dikarenakan ada Covid- 19 masih memberikan dampak signifikan terhadap pendapatan asli daerah Kota Padang tahun 2020-2024. Rasio kontribusi pajak daerah dalam upaya peningkatan pendapatan asli daerah Kota Padang tahun 2020- 2024 berada dalam kategori sangat baik. Dapat disimpulkan bahwa perkembangan efektivitas dan kontribusi pajak daerah dalam upaya peningkatan pendapatan asli daerah Kota Padang semakin membaik dari tahun ke tahun. Pemerintah Kota Padang diharapkan menggali lebih lanjut potensi daerah dalam upaya peningkatan pengumpulan pajak daerah agar semakin efektif dari tahun ke tahun, sehingga pajak daerah memberikan kontribusi yang besar dalam Pendapatan Asli Daerah Kota Padang